Relationship between Infectious Diseases, Maternal Nutritional Knowledge and Dietary Patterns with the Incident of Stunting in Toddlers in the Working Area of the Kapoiala Health Center, Konawe Regency, Southeast Sulawesi Province: - - Rasmaniar, Rasmaniar; Sapitri, Anggi; leksono, Purnomo; Petrus, Petrus; fathurrahman, Teguh; Rai sudarsono, I made; atoy, Lena (Poltekkes Kemenkes Kendari, 2023)
Background: Stunting is a disorder of growth and brain development in children caused by malnutrition for a long time, including inadequate intake and increased nutritional needs due to repeated infections, and lack of stimulation. The percentage of stunted toddlers in Southeast Sulawesi in 2017 was 36.4% , Konawe Regency by 29.6%. This study aims to determine the relationship between infectious diseases, knowledge of maternal nutrition and diet with the incidence of stunting under five children Method :. This type of research is descriptive analytical research with a cross sectional study approach. It was carried out from March to May 2020, the number of samples was 35 participant. The sampling technique was Proportional Random Sampling. Results: The study showed as many as 54.3% (n=19) under five were women, 57.1% under five aged 12-36 months, 31.4% under five suffering from infectious diseases, there were 85.7% mothers under five had poor nutrition knowledge, as many as 51.4% Stunting toddlers. Conclusion: There is a significant relationship between infectious diseases and the incidence of stunting in toddlers, and there is no significant relationship between knowledge of maternal nutrition and eating patterns with the incidence of stunting. Suggestion: Toddler mothers are given nutrition education to always visit Posyandu regularly so they can monitor their child's growth and development.